Risk of Fungi Associated with Aflatoxin and Fumonisin in Medicinal Herbal Products in the Kenyan Market - Lucia Keter; Richard Too; Nicholas Mwikwabe; Charles Mutai; Jennifer Orwa; Lizzy Mwamburi; Stanley Ndwigah; Christine Bii; Richard Korir (The Scientific World Journal, 2017)
Utilization of herbal products is a major concern due to the possibility of contamination by toxigenic fungi that are mycotoxin producers such as Aspergillus species during processing and packaging. Research was carried out to determine the presence of aflatoxins and fumonisins in herbal medicinal products sold in Eldoret and Mombasa towns in Kenya. The study employed both exploratory and laboratory experimental design. The herbal products were purchased from the market and transported to Kenya Medical Research Institute for processing and analysis. Fungal contaminants were determined according to Pharmacopoeia specifications. The toxins were quantified using ELISA based technique. The genus Aspergillus was the most dominant followed by Penicillium. Fungal counts ranged between 1 CFU/g and >1000 cfu/g. Analysis of variance showed that the rate of fungal contaminants for Eldoret and Mombasa samples had significant association (p≤0.001). Aflatoxin levels ranged from 1 to 24 ppb, while fumonisin levels ranged from 1 to >20 ppb. Only 31% of samples met the standards for microbial limits as specified in Pharmacopoeia. There is need for product microbial quality improvement through proper harvesting, processing, storage, and marketing. It is recommended that a policy be enacted to enable regulation of herbal products in Kenya.